2022
DOI: 10.3389/fimmu.2022.975848
|View full text |Cite
|
Sign up to set email alerts
|

Discovering common pathogenetic processes between COVID-19 and sepsis by bioinformatics and system biology approach

Abstract: Corona Virus Disease 2019 (COVID-19), an acute respiratory infectious disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has spread rapidly worldwide, resulting in a pandemic with a high mortality rate. In clinical practice, we have noted that many critically ill or critically ill patients with COVID-19 present with typical sepsis-related clinical manifestations, including multiple organ dysfunction syndrome, coagulopathy, and septic shock. In addition, it has been demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 90 publications
(107 reference statements)
0
27
0
Order By: Relevance
“…The results showed that TFs (FOXC1, YY1, GATA2, SREBF1 and FOXL1) were associated with CXCR4, CXCL1, COL6A3, COL1A2 and ITGA6 and miRNAs (hsa-mir-1-3p, hsa-mir-26b-5p, hsa-mir-29b-3p, hsa-mir-105-5P and hsa-mir-4781-5P) were closely regulated with THBS2, SOX9, THY1, COL1A2 and TIMP. In previous bioinformatics analyses, Ahmed, Islam, and Lu Lu et al found FOXC1, YY1, GATA2, and FOXL1 are significant TFs for COVID-19 (6,49,50). Pharmacological studies have also found that SREBF1, as a key regulator of lipid-metabolizing enzymes connected closely with the procession of AH, is the transcription factor most activated by several effective antiviral drugs in vitro and may become A pivot therapeutic spot for both AH and COVID-19 (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that TFs (FOXC1, YY1, GATA2, SREBF1 and FOXL1) were associated with CXCR4, CXCL1, COL6A3, COL1A2 and ITGA6 and miRNAs (hsa-mir-1-3p, hsa-mir-26b-5p, hsa-mir-29b-3p, hsa-mir-105-5P and hsa-mir-4781-5P) were closely regulated with THBS2, SOX9, THY1, COL1A2 and TIMP. In previous bioinformatics analyses, Ahmed, Islam, and Lu Lu et al found FOXC1, YY1, GATA2, and FOXL1 are significant TFs for COVID-19 (6,49,50). Pharmacological studies have also found that SREBF1, as a key regulator of lipid-metabolizing enzymes connected closely with the procession of AH, is the transcription factor most activated by several effective antiviral drugs in vitro and may become A pivot therapeutic spot for both AH and COVID-19 (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils, as "professional" phagocytes, possess a large number of antibacterial "weapons" in their granules, allowing them to destroy pathogens during phagocytosis. During the degranulation process, bactericidal enzymes can also be released from the cell (37).The mechanism of this process leading to SARS-CoV-2 exists in the process of neutrophil extracellular traps (NETs) modified by bactericidal proteins in granules and cytoplasm, which indicates that we can disrupt the vicious cycle of hepatocellular inflammation in patients with new coronary pneumonia by activating neutrophils and promoting the formation of NETs (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that TFs (FOXC1, YY1, GATA2, SREBF1, and FOXL1) were associated with CXCR4, CXCL1, COL6A3, COL1A2, and ITGA6 and miRNAs (hsa‐mir‐1‐3p, hsa‐mir‐26b‐5p, hsa‐mir‐29b‐3p, hsa‐mir‐105‐5P, and hsa‐mir‐4781‐5P) were closely regulated with THBS2, SOX9, THY1, COL1A2, and TIMP. In previous bioinformatics analyses, Ahmed, Islam, and Lu Lu et al found FOXC1, YY1, GATA2, and FOXL1 are significant TFs for COVID‐19 37,50,51 . Pharmacological studies have also found that SREBF1, as a key regulator of lipid‐metabolizing enzymes connected closely with the procession of AH, is the transcription factor most activated by several effective antiviral drugs in vitro and may become A pivot therapeutic spot for both AH and COVID‐19 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…5 Severe COVID-19 frequently presents pathologically with pulmonary and extra-pulmonary organ dysfunction. 6 Previous research suggested that the lungs are the organs most affected by the way of the novel coronavirus accompanied with a massive quantity of immune cell activation and the release of inflammatory factor. 7,8 Extrapulmonary organs, on the other hand, have varying levels of tissue injury and inflammatory response, demonstrated as multiorgan dysfunction and systematic inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%